Prohormones in the Early Diagnosis of Cardiac Syncope. Issue 12 (21st December 2017) - Badertscher, Patrick; Nestelberger, Thomas; de Lavallaz, Jeanne du Fay; Than, Martin; Morawiec, Beata; Kawecki, Damian; Miró, Òscar; López, Beatriz; Martin‐Sanchez, F. Javier; Bustamante, José; Geigy, Nicolas; Christ, Michael; et al.
Abstract : Background: The early detection of cardiac syncope is challenging. We aimed to evaluate the diagnostic value of 4 novel prohormones, quantifying different neurohumoral pathways, possibly involved in the pathophysiological features of cardiac syncope: midregional–pro‐A‐type natriuretic peptide (MRproANP), C‐terminal proendothelin 1, copeptin, and midregional‐proadrenomedullin. Methods and Results: We prospectively enrolled unselected patients presenting with syncope to the emergency department (ED) in a diagnostic multicenter study. ED probability of cardiac syncope was quantified by the treating ED physician using a visual analogue scale. Prohormones were measured in a blinded manner. Two independent cardiologists adjudicated the final diagnosis on the basis of all clinical information, including 1‐year follow‐up. Among 689 patients, cardiac syncope was the adjudicated final diagnosis in 125 (18%). Plasma concentrations of MRproANP, C‐terminal proendothelin 1, copeptin, and midregional‐proadrenomedullin were all significantly higher in patients with cardiac syncope compared with patients with other causes ( P <0.001). The diagnostic accuracies for cardiac syncope, as quantified by the area under the curve, were 0.80 (95% confidence interval [CI], 0.76–0.84), 0.69 (95% CI, 0.64–0.74), 0.58 (95% CI, 0.52–0.63), and 0.68 (95% CI, 0.63–0.73), respectively. In conjunction with the ED probability (0.86; 95% CI, 0.82–0.90), MRproANP, but not the other prohormone, improved the area under the curve to 0.90 (95% CI, 0.87–0.93), which was significantly higher than for the ED probability alone ( P =0.003). An algorithm to rule out cardiac syncope combining an MRproANP level of <77 pmol/L and an ED probability of <20% had a sensitivity and a negative predictive value of 99%. Conclusions: The use of MRproANP significantly improves the early detection of cardiac syncope among unselected patients presenting to the ED with syncope. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01548352.